A classification for Blechnaceae (Polypodiales: Polypodiopsida): New genera, resurrected names, and combinations - Gasper, André Luís De; Dittrich, Vinícius Antonio De Oliveira; Smith, Alan Reid; Salino, Alexandre (Phytotaxa, 2016)
The fern family Blechnaceae, with about 250 species, has traditionally comprised one large genus, Blechnum, plus seven to nine smaller genera, most with fewer than 10 species. Several phylogenetic analyses strongly suggest that Blechnum in the traditional sense is not a monophyletic group. We propose a new classification for the family, with three subfamilies and 24 genera. All genera are described and new combinations are provided, with an estimate of species number for each genus. We also provide a key for the identification of the genera.